2005
DOI: 10.1111/j.1369-7625.2005.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

A consultation leaflet to improve an older patient's involvement in general practice care: a randomized trial

Abstract: Objective To evaluate the effects of a programme to enhance the involvement of older patients in their consultations in general practice.Design Cluster randomized trial, in which data was collected from different cohorts.Setting and participants Twenty-five general practices in the southeast part of the Netherlands and their patients aged 70 years and over.Intervention Patients in the intervention group received a leaflet to help them prepare for the consultation. General practitioners (GPs) received an outrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…Emotional support from the surgeon was negatively related to perceptions of being the final decision-maker, but not associated with patient questioning of surgeons [39]. Other findings revealed that in an intervention group, users of an information leaflet reported more psychological symptoms to their general practitioner compared with non-users [35]. No other differences in underreported health problems were found and the prevalence of chronic diseases was similar.…”
Section: Emotional and Psychological Symptoms Associated With Difficumentioning
confidence: 55%
See 4 more Smart Citations
“…Emotional support from the surgeon was negatively related to perceptions of being the final decision-maker, but not associated with patient questioning of surgeons [39]. Other findings revealed that in an intervention group, users of an information leaflet reported more psychological symptoms to their general practitioner compared with non-users [35]. No other differences in underreported health problems were found and the prevalence of chronic diseases was similar.…”
Section: Emotional and Psychological Symptoms Associated With Difficumentioning
confidence: 55%
“…No other differences in underreported health problems were found and the prevalence of chronic diseases was similar. However, users of the information leaflet were more accustomed to preparing themselves for the consultation than non-users [35]. A significant drop in anxiety immediately after the consultation was revealed, but there is no evidence that this reduction varied between the two groups [36].…”
Section: Emotional and Psychological Symptoms Associated With Difficumentioning
confidence: 89%
See 3 more Smart Citations